Investigational drugs in Phase II clinical trials for the treatment of obesity: implications for future development of novel therapies. (August 2014) - Jackson, V Margaret; Price, David A; Carpino, Philip A
<x xml:space="preserve">Abstract</x> Introduction: The discovery of new antiobesity agents has attracted considerable interest over the past decade, but many of the investigational agents that have advanced into human clinical trials have shown unacceptable adverse events and/or efficacy profiles. Areas covered: This review summarizes the available preclinical and clinical data of antiobesity drugs currently in Phase II clinical trials. It also provides a brief summary of the mechanisms underlying the regulation of energy homeostasis. Expert opinion: New approaches to solving the obesity epidemic are needed, exemplified in part by some of the agents currently in Phase II clinical trials. Weight loss treatments could be tailored to specific subpopulations such as morbidly obese individuals with a high risk for complications or obese patients with a specific genotype. Fixed dose combinations of drugs that target multiple complementary pathways could be developed to deliver durable, 10% or greater weight loss. A shift away from pharmacological agents that act on pathways in the CNS could lead to drugs with fewer side effects and more favorable risk/benefit ratios.